Pendapatan dan Religiusitas Individu Muslim di Indonesia - Irsyad Hawari (ITB AAS INDONESIA Surakarta, 2023)
Numerous studies have revealed a negative relationship between economics and religiosity, suggesting that an improvement in economic conditions can decrease an individual's religiosity. This assumption is based on the hypothesis of secularism, which posits that economic progress reduces religious adherence. The present study aims to examine the influence of economic variables, measured by individual income and daily working hours, on the religiosity of Muslim communities in Indonesia, as measured by participation in religious study groups (taklim) and prayer activities. A quantitative analysis using logistic regression is employed to explore the likelihood of individual religiosity levels when influenced by economic variables. Control variables in this study include age, proximity to Islamic traditions, level of adherence, place of residence, and Islamic education. The research findings indicate that income level does not significantly increase the likelihood of individuals engaging in prayer and taklim activities. Conversely, the number of daily working hours exhibits a negative relationship with prayer and taklim activities. The longer an individual works in a day, the higher the likelihood of abstaining from prayer and taklim activities.